Peningkatan Kecakapan Berkomunikasi Dan Hasil Belajar PKn Siswa Kelas 6 dengan Talking Stick Berbantuan Salindia - Hana Septina Kristanti (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
This study aims to improve communication skills and learning outcomes of Civics in Grade 6 students of SDN Dukuh 03 Salatiga with the application of the Talking Stick assisted h slideshow. This type of research is classroom action research. The location (setting) in this study is grade 6 SDN Dukuh 03 Salatiga. The subjects of the study were 28 students in 6th grade. The object of this research is communication skills and Civics learning outcomes. This research was carried out in 2 cycles. This study was declared successful if the average achievement of indicators of communication skills and classical completeness of student learning outcomes in the good category (60% -75%), very good (76% -99%), or special (100%). The results of the study show that the implementation of the slideshow-assisted Talking Stick in the Civics learning process can improve communication skills and Civics learning outcomes. The communication skills have increased by 23.8% from pre-cycle to cycle 1 meeting 1. Cycle 1 meeting 2 increased 8.34% from cycle 1 meeting 1. Students' communication skills increased from cycle 1 meeting 2 to cycle 2 meeting 1 by 6.75%. Increased again by 7.93% from cycle 2 meeting 1 to cycle 2 meeting 2. Increased student communication skills proved to be able to improve student learning outcomes in Civics learning. In the pre cycle, only 13 students (46.43%) were completed, the remaining 15 students (53.57%) were not completed. In cycle 1, there were 16 students (57.14%) completed, while 12 students (42.86%) were not completed. After the cycle 2 action was carried out, as many as 22 students (78.57%) were completed and 6 students (21.43%) were not completed.